Mantle flow through a tear in the Nazca slab inferred from shear wave splitting - Colton Lynner; Megan L. Anderson; Daniel E. Portner; Susan L. Beck; Hersh Gilbert (Geophysical Research Letters)
Abstract A tear in the subducting Nazca slab is located between the end of the Pampean flat slab and normally subducting oceanic lithosphere. Tomographic studies suggest mantle material flows through this opening. The best way to probe this hypothesis is through observations of seismic anisotropy, such as shear wave splitting. We examine patterns of shear wave splitting using data from two seismic deployments in Argentina that lay updip of the slab tear. We observe a simple pattern of plate‐motion‐parallel fast splitting directions, indicative of plate‐motion‐parallel mantle flow, beneath the majority of the stations. Our observed splitting contrasts previous observations to the north and south of the flat slab region. Since plate‐motion‐parallel splitting occurs only coincidentally with the slab tear, we propose mantle material flows through the opening resulting in Nazca plate‐motion‐parallel flow in both the subslab mantle and mantle wedge.